Al Dobowi Group: Business Growth in Local and International Markets - Hanaysha, Jalal (IIUM Journal of Case Studies in Management, 2025)
Al Dobowi Group was established in 1976 to serve customers in the UAE and other international markets by offering various products of high-quality at affordable prices. The Group runs its operations internationally in four continents (Middle East, Africa, Europe, and the Americas) and currently employs over 2000 staff, focusing on providing unique products and services to its customers in target markets. The main products offered include tyres, retreads, industrial and automotive batteries, industrial rubber products and fabrication, fluid management, autoparts, oil, filter, lubricants, storage and material handling, garage equipment, and industrial UPS and inverters. This case study aims to improve our understanding about the historical growth and development of Al Dobowi Group. It also enhances our understanding about the key tactics employed for managing its foreign operations. A significant focus is further put on the marketing mix strategies employed to achieve success in both domestic and international markets. Additionally, the corporate social responsibility and contributions of Al Dobowi Group to charitable organizations are outlined. Finally, this case study ends by highlighting the key challenges confronted by Al Dobowi Group in both domestic and international markets.